2013
DOI: 10.1016/j.appet.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

When chefs adopt a school? An evaluation of a cooking intervention in English primary schools

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractThis article sets out the findings from research on the impact of a, UK based, chefs in schools teaching programme on food, provenance, health, nutrition and cookery. Professional chefs link with local schools, where they deliver up to three sessions to one class over a year.The research measured the impact of a standardised intervention package and change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(140 citation statements)
references
References 16 publications
4
129
1
2
Order By: Relevance
“…This might include teaching cooking skills from an early age by re-introducing a home economics curriculum in schools to build cooking skills, knowledge and confidence (31)(32)(33) . Inclusion of cooking skills into nutrition education has been shown to be effective at improving cooking self-efficacy, fostering healthy eating habits, and is an important supplement to traditional nutrition education (34,35) . Some evidence exists to support this approach, as prior research has shown that cooking skills education through cooking classes and engagement in food preparation activities in adolescence can lead to more healthful diet behaviours (12,(36)(37)(38) .…”
Section: Discussionmentioning
confidence: 99%
“…This might include teaching cooking skills from an early age by re-introducing a home economics curriculum in schools to build cooking skills, knowledge and confidence (31)(32)(33) . Inclusion of cooking skills into nutrition education has been shown to be effective at improving cooking self-efficacy, fostering healthy eating habits, and is an important supplement to traditional nutrition education (34,35) . Some evidence exists to support this approach, as prior research has shown that cooking skills education through cooking classes and engagement in food preparation activities in adolescence can lead to more healthful diet behaviours (12,(36)(37)(38) .…”
Section: Discussionmentioning
confidence: 99%
“…Interactive food activities can positively impact children's food awareness, eating and cooking enjoyment, and fruit and vegetable preferences. (Chu et al, 2013), (Caraher, Seeley, Wu, & Lloyd, 2013), (Van der Horst, Ferrage, & Rytz, 2014), (Cunningham-Sabo and Lohse, 2014) As well as valuable food skills, children develop a closer connection to and ownership of food. A recent systematic review of cooking programmes reported the positive influence these activities may exert on children's food preferences, attitudes and behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Los beneficios de la involucración directa en la preparación de alimentos -y de la educación en habilidades culinarias en niños, adolescentes y adultos-, encontrados en la literatura científica hasta el momento son: -La mejora en las conductas, actitudes y creencias alimentarias [26][27][28][29][30] .…”
Section: La Educación Nutricional Culinariaunclassified
“…Los elementos de efectividad de los programas de educación nutricional infantil: la educación nutricional culinaria y sus beneficios -El incremento del consumo de frutas 38,39 , verduras 27,40 o de ambos 26,30,31,[41][42][43][44] .…”
Section: La Educación Nutricional Culinariaunclassified